2017
DOI: 10.1515/rjim-2017-0022
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of nitrite/nitrate, lipid profile, and Fasting Plasma Glucose and their associations in subclinical hypothyroid women before and after a two month treatment by levothyroxine

Abstract: Background. Subclinical hypothyroidism (sHT) is a condition defined by elevated TSH values with normal levels of free thyroid hormones. Altered metabolic status is one of the consequences of sHT which can affect serum levels of FPG, lipid profile, and nitric oxide which propounds cardiovascular consequences per se. The aim of this study was to determine the possible effects of sHT on nitrite/nitrate levels, as a marker of endothelial performance.Materials and Methods. 50 females were enrolled in this study, 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…This condition may ultimately lead to arterial obstruction, blood clot formation and myocardial infarction (MI) or stroke in severe circumstances. Therefore, controlling dietary intake of lipids and serum levels of lipid fractions, particularly cholesterol is an important approach for prevention of diabetic complications (9,10). In addition, elevation of triglyceride (TG) or triacylglycerole is another known risk factor for CVD (11).…”
Section: Introductionmentioning
confidence: 99%
“…This condition may ultimately lead to arterial obstruction, blood clot formation and myocardial infarction (MI) or stroke in severe circumstances. Therefore, controlling dietary intake of lipids and serum levels of lipid fractions, particularly cholesterol is an important approach for prevention of diabetic complications (9,10). In addition, elevation of triglyceride (TG) or triacylglycerole is another known risk factor for CVD (11).…”
Section: Introductionmentioning
confidence: 99%
“…Hashemi et al measured the levels of fasting blood glucose (FPG), lipid profile components, and nitric oxide by spectrophotometry on 50 women (25 healthy groups and 25 hypothyroid patients). They found that nitric www.nature.com/scientificreports/ oxide was significantly different from LDL in the two groups, but it was not significantly different for other components 54 .…”
Section: Discussion and Resultsmentioning
confidence: 98%
“…Hashemi et al measured the levels of fasting blood glucose (FPG), lipid pro le components, and nitric oxide by spectrophotometry on 50 women (25 healthy groups and 25 hypothyroid patients). They found that nitric oxide was signi cantly different from LDL in the two groups, but it was not signi cantly different for other components (55).…”
Section: Comparison Of Serum No Correlation and Components Of Metabol...mentioning
confidence: 94%